EXPLORING THE APPLICATION OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGIES IN THE FASHION INDUSTRY: A CASE OF GARMENT CONSTRUCTION IN KUMASI, GHANA. - Opoku, Moses; Dickson, Adom; Baiden, Sarah; Oppong, Diana; Isemikon Cyril-Egware, Pamela (Penerbit Lafadz Jaya, 2024)
This study explores the use of artificial intelligence (AI) technologies in the fashion industry, specifically focusing on garment construction in Ghana. Again, it examines how AI impacts key stages of garment production, including style development, body measurements, pattern making, lay planning, cutting, assembling, and packaging. It employed both quantitative data from surveys and qualitative insights from interviews with fashion designers, manufacturers, and industry experts. The findings indicate that AI technologies are most widely adopted in style development and pattern making, where they significantly enhance design efficiency and precision. However, adoption rates are lower in cutting, assembling, and packaging due to high initial costs and technical complexity. The study also identifies significant barriers to AI adoption, such as financial constraints, lack of technical expertise, and cultural resistance to change. The implications of these findings suggest that AI technologies have the potential to transform garment construction processes, improve efficiency, reduce waste, and increase competitiveness in the fashion industry. This study contributes to the existing literature by providing empirical data on AI adoption in the Ghanaian fashion industry, and clearly indicates the need for future study to explore regional differences, long-term impacts, and strategies to integrate AI technologies while preserving traditional craftsmanship in garment making.